Analysis of infant cry using Short Time Fourier Transform (STFT) / Zaidi Shaari - Shaari, Zaidi (2007)
Crying is the only method of communication for an infant's to express their needs and feelings. The information regarding the state of an infant, such as hunger or pain, can be determined from an infant's cry. This study focuses on the analysis of the cry signals (hunger, pain) to obtain information that can be used to classify the signal automatically. STFT was used to extract the information embedded in both cry signals. The pain cry produced more intense and longer duration than hunger cry. Hunger cry however, can be classified to have consistent shift pattern. These were key characteristics that can be used for an early classification method for both type of cry.